Differential Macrophage Polarization from Pneumocystis in Immunocompetent and Immunosuppressed Hosts: Potential Adjunctive Therapy during Pneumonia - Nandakumar, Vijayalakshmi (Infect Immun, 2017)
We explored differential polarization of macrophages during infection using a rat model of Pneumocystis pneumonia. We observed enhanced pulmonary M1 macrophage polarization in immunosuppressed (IS) hosts, but an M2 predominant response in immunocompetent (IC) hosts following Pneumocystis carinii challenge. Increased inflammation and inducible nitric oxide synthase (iNOS) levels characterized the M1 response. However, macrophage ability to produce nitric oxide was defective. In contrast, the lungs of IC animals revealed a prominent M2 gene signature, and these macrophages effectively elicited an oxidative burst associated with clearance of Pneumocystis. In addition, during P. carinii infection the expression of Dectin-1, a critical receptor for recognition and clearance of P. carinii, was upregulated in macrophages of IC animals but suppressed in IS animals. In the absence of an appropriate cytokine milieu for M2 differentiation, Pneumocystis induced an M1 response both in vitro and in vivo. The M1 response induced by P. carinii was plastic in nature and reversible with appropriate cytokine stimuli. Finally, we tested whether macrophage polarization can be modulated in vivo and used to help manage the pathogenesis of Pneumocystis pneumonia by adoptive transfer. Treatment with both M1 and M2 cells significantly improved survival of P. carinii-infected IS hosts. However, M2 treatment provided the best outcomes with efficient clearance of P. carinii and reduced inflammation.